Sickle cell health awareness, perspectives, and experiences (SHAPE) survey: perspectives of adolescent and adult patients, caregivers, and healthcare professionals on the burden of sickle cell disease - Montalembert, Mariane de; Anderson, Alan; Costa, Fernando F.; Inusa, Baba P. D.; Jastaniah, Wasil; Kunz, Joachim; Tinga, Biba; Ingoli, Elvie; James, John; Hartfield, Regina; Beaubrun, Anne; Lartey, Belinda; et al. (European journal of haematology, 2024)
Objectives Sickle cell disease (SCD) is an inherited disorder that causes lifelong complications, substantially impacting the physical and emotional well-being of patients and their caregivers. Studies investigating the effects of SCD on quality of life (QOL) are often limited to individual countries, lack SCD-specific QOL questionnaires, and exclude the caregiver experience. The SHAPE survey aimed to broaden the understanding of the global burden of SCD on patients and their caregivers and to capture the viewpoint of healthcare providers (HCPs). Methods A total of 919 patients, 207 caregivers, and 219 HCPs from 10, 9, and 8 countries, respectively, answered a series of closed-ended questions about their experiences with SCD. Results The symptoms most frequently reported by patients were fatigue/tiredness (84%) and pain/vaso-occlusive crises (71%). Patients' fatigue/tiredness had one of the greatest impacts on both patients' and caregivers' QOL. On average, patients and caregivers reported missing 7.5 days and 5.0 days per month, respectively, of school or work. HCPs reported a need for effective tools to treat fatigue/tiredness and a desire for more support to educate patients on long-term SCD-related health risks. Conclusions The multifaceted challenges identified using the SHAPE survey highlight the global need to improve both patient and caregiver QOL.
Online veröffentlicht am 18. April 2024
Gesehen am 23.09.2024